\(In vitro\) antioxidant, α-amylase and α-glucosidase inhibitory activities of endophytic bacteria from the roots of the mangrove plant \(Rhizophora stylosa\) Griffith - Dat, Ton That Huu; Phung Thi Thuy, Oanh (Academia Journal of Biology, 2021)
Mangrove is one of the highly productive ecosystems and contains diverse plants and microbial communities. Bacterial endophytes from mangroves are considered as a prolific source of biological molecules with important functions in the protection of mangrove plants against herbivores, insects as well as pathogens. The present study aimed to isolate endophytic bacteria from the roots of mangrove plant Rhizophora stylosa and to screen antioxidant,